Survival, growth and regeneration of forest species in mining areas in the Eastern Amazonia - Martins, Walmer Bruno Rocha; Barros, Welton dos Santos; Dionisio, Luiz Fernandes Silva; Bezerra, Talita Godinho; Santos, Mario Lima dos; Ferreira, Gracialda Costa; Barbosa, Victor Moreira; Oliveira, Francisco de Assis (Scientia Plena, 2020)
Planting forest saplings is the most usual method for restoring areas degraded by mining. Therefore, the objective of this study was to evaluate the survival growth of planted forest species and spontaneous regeneration in post-bauxite mining areas. For this purpose, we sampled plots in recovery areas with ages ranging from five to nine years, in which the establishment, recruitment, mean annual increase in diameter and total height of the species were evaluated. The species were further classified for conservation status and origin. Of the 156 species found, 18 presented less than 25% of survival and were therefore not recommended for use in the areas, while another 22 planted species showed more than 55% survival, indicating that they can be used. Five species were registered with some threat level, another nine species were registered as exotic to Brazil and four to the Amazon. In general, 35 species were classified as suitable for planting, with an acceptable mortality rate and satisfactory growth. Thus, it was possible to select those most suitable for planting the post mining area through an evaluation of the survival rate and growth of the species.